The reivers : a reminiscence - Faulkner, William, 1897-1962. (New York : Vintage Books, 1992)
One day in 1905, eleven-year-old Lucius is persuaded by Boon Hogganbeck to "borrow" his grandfather's car. Ned McCaslin, a black man, stows away in the car and the three embark on an odyssey which ends at Miss Reba's bordello.
Pulitzer Prize.
Wilson's Fiction.
Wilson's Senior High School.
Adult
Keywords: Bildungsromans; Humorous fiction; Southern States -- Fiction; Southern States -- Fiction; Bildungsromane; Humorous stories